2010
DOI: 10.1073/pnas.0908801107
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD73 antibody therapy inhibits breast tumor growth and metastasis

Abstract: Extracellular adenosine is a potent immunosuppressor that accumulates during tumor growth. We performed proof-of-concept studies investigating the therapeutic potential and mechanism of action of monoclonal antibody (mAb)-based therapy against CD73, an ecto-enzyme overexpressed on breast-cancer cells that catalyzes the dephosphorylation of adenosine monophosphates into adenosine. We showed that anti-CD73 mAb therapy significantly delayed primary 4T1.2 and E0771 tumor growth in immune-competent mice and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
544
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(569 citation statements)
references
References 48 publications
25
544
0
Order By: Relevance
“…This result is in agreement with the literature that shows the increase of ecto-5′-NT/CD73 expression in many other cancers such as breast cancer, glioma, and melanoma [19,23,56]. Furthermore, ecto-5′-NT/CD73 overexpression promotes invasion, migration, adhesion, and metastasis of human breast cancer cells [20,57], indicating higher invasiveness and metastatic capability to melanomas [56,58] and poor prognosis in human colorectal cancer [22]. Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with the literature that shows the increase of ecto-5′-NT/CD73 expression in many other cancers such as breast cancer, glioma, and melanoma [19,23,56]. Furthermore, ecto-5′-NT/CD73 overexpression promotes invasion, migration, adhesion, and metastasis of human breast cancer cells [20,57], indicating higher invasiveness and metastatic capability to melanomas [56,58] and poor prognosis in human colorectal cancer [22]. Ecto-5′-NT/CD73 expression in cancer cells has been also linked with drug resistance [26,59] and immune escape [44,60].…”
Section: Discussionsupporting
confidence: 93%
“…The final dephosphorylation of nucleotides, conversion of nucleoside monophosphates (e.g., AMP) to their respective nucleosides (e.g., adenosine), is catalyzed by ecto-5′-nucleotidase/CD73 (ecto-5′-NT/CD73). This enzyme is highly expressed in a variety of solid tumors [19][20][21][22] and has both its enzymatic activity and its adhesion protein function associated with cancer progression [23,24]. Besides, ecto-5′-NT/CD73 was found to be involved in cancer cell growth, maturation, differentiation, adhesion, migration, invasiveness, metastasis, immune escape, and drug resistance [19,[21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Stagg et al and Zhou et al found that CD73, the ectoenzyme responsible for endogenous adenosine formation, contributes to breast cancer metastasis [15][16][17]. In agreement with these reports, we found that MDA-MB-231 cells overexpress CD73 and differ from HMEC in that they possess more efficient means than HMEC to hydrolyze extracellular ATP to adenosine (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the ATP breakdown product adenosine can activate calcium signaling in MDA-MB-231 breast cancer cells, and the ectonucleotidase C D 7 3 , w h i c h c o n v e r t s e x t r a c e l l u l a r a d e n o s i n e monophosphate (AMP) to adenosine, was shown to promote breast cancer growth and metastasis [15][16][17]. In light of our previous work, these reports support the concept that purinergic signaling can indeed contribute to the motility and metastasis of breast cancer cells.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…promoting functions in breast cancer (16). In breast-cancer cells, CD73 expression has been shown to be regulated by estrogen receptors (ER), whereby loss of ER significantly enhances CD73 expression (17).…”
Section: Discussionmentioning
confidence: 99%